Additions to the Indonesian crab fauna of the genus Mariaplax Rahayu & Ng, 2014, and notes on Hexapus timika Rahayu & Ng, 2014 (Crustacea, Decapoda, Brachyura, Hexapodidae) - Rahayu, Dwi Listyo; Widyastuti, Ernawati (Zootaxa, 2018)
Hexapus timika Rahayu & Ng, 2014 is redescribed based on newly collected male and female specimens from Papua, Indonesia. Three new species from Jakarta Bay and Sunda Strait, Indonesia, are added to the genus Mariaplax, the richest genus in the family Hexapodidae, hitherto having 14 species. Mariaplax pitrai n. sp. has the carapace covered by small, closely-spaced tubercles and long ambulatory legs, resembling M. chenae Rahayu & Ng, 2014 but easily separated by the position of female vulvae. Mariaplax hispida n. sp. is unique for the presence of short stiff setae on the outer face of the chelipeds and pereopods 2−4. Mariaplax sundaica n. sp. is characterized by the broad carapace, covered entirely by tubercles, the longitudinal grooves present only on the meri of pereopods 2 and 3. A key to the species of Mariaplax is provided.